2021
DOI: 10.2147/ijn.s290438
|View full text |Cite|
|
Sign up to set email alerts
|

Application of Radiosensitizers in Cancer Radiotherapy

Abstract: Radiotherapy (RT) is a cancer treatment that uses high doses of radiation to kill cancer cells and shrink tumors. Although great success has been achieved on radiotherapy, there is still an intractable challenge to enhance radiation damage to tumor tissue and reduce side effects to healthy tissue. Radiosensitizers are chemicals or pharmaceutical agents that can enhance the killing effect on tumor cells by accelerating DNA damage and producing free radicals indirectly. In most cases, radiosensitizers have less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
191
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(194 citation statements)
references
References 216 publications
(98 reference statements)
1
191
0
2
Order By: Relevance
“…Radioresistance remains to be a major obstacle in the management of cancer patients. Although various studies investigated to identify novel and better radiosensitizers for the cancer treatment, the result still cannot reach clinical translation [71]. Our results revealed that nCRT-induced mRNA expression of CXCL12, CXCR4, and FAPα in LARC.…”
Section: Discussionmentioning
confidence: 68%
“…Radioresistance remains to be a major obstacle in the management of cancer patients. Although various studies investigated to identify novel and better radiosensitizers for the cancer treatment, the result still cannot reach clinical translation [71]. Our results revealed that nCRT-induced mRNA expression of CXCL12, CXCR4, and FAPα in LARC.…”
Section: Discussionmentioning
confidence: 68%
“…The antitumor immunity activated by H@Gd-NCPs can further be strengthened by immune checkpoint blockade therapy against primary, distant, and metastatic tumors. Another approach to address hypoxic environmental impact on RT is to utilize nitric oxide (NO) prodrugs, shown to be efficient radiosensitizers as cell respiration inhibitors, and co-delivery with exogenous oxygen resources [ 348 , 349 ]. Recent work has shown potential solution to this obstacle through a hybrid semiconducting organosilica-based O 2 nanoeconomizer which in an acidic tumor environment releases NO and, via mild photothermal treatment, releases O 2 resulting in enhanced efficacy of radiotherapy in vitro and in vivo [ 350 ].…”
Section: Cancer Radiation Therapymentioning
confidence: 99%
“…Insufficient H 2 O 2 in the tumor microenvironment (TME) is a profound problem for MnCO-based cancer therapy. CPT is a natural product topoisomerase inhibitor operating via several mechanisms including induction of cellular DNA damage (14)(15)(16). It is also an H 2 O 2 enhancer, inducing high levels of H 2 O 2 in the tumor (14).…”
Section: Introductionmentioning
confidence: 99%